Business analysis with Microsoft Excel - Carlberg, Conrad George (Que Pub., 2007)
Whether you own a small business or work for a large corporation - whether you are looking for help making financial and business decisions - this book is for you. Business Analysis with Microsoft® Excel, Third Edition, provides in-depth information that will streamline your use of the tools within Excel. Professional advice and guidance from an experienced author provide the answers to your most pressing questions: What's the relationship between my cost of goods sold and my inventory? How do I get Excel to keep these values up-to-date on my income statement and my balance sheet? I have to track service quality over time. How can I automate that using Excel charts? How can I forecast future demand for my products, based on prior sales results? What's the difference between financial leverage and operating leverage? How do I calculate them using my financial records? I need to project my financials for next year. Does Excel have a tool for that? What do I need to know to use it effectively? How do I do all these things using the new Ribbon in Excel 2007? What are the best ways to automate a connection between Excel and an external database? Category Spreadsheets Covers Applicable for versions of Microsoft Excel 97 to 2007 User Level. Intermediate-Advanced More great stuff is just a click away! Sample journals and ledgers; examples of trial balances, income statements, and balance sheets; Custom functions, such as FIFO and LIFO, for inventory management; VBA routines that automate the creation of forecasts, quality control charts, and sales and marketing analysis; Statistical process control charts: P charts, X-and-S charts, X-and-MR charts; Forecasting tools: Seasonal smoothing and ARIMA model identification quote from the front cover "Conrad takes the time to give the readers an easy-to-follow step-by-step understanding of the material, accompanied by clear illustrations, making this an excellent book to learn the material. I recommend this book to anyone wanting to gain more expertise in using and manipulating business data from within Excel."--Bob Umlas, Excel MVP